2021
DOI: 10.3892/or.2021.8080
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate transporter NBCe1 regulates proliferation and viability of human prostate cancer cells LNCaP and PC3

Abstract: Studies on cultured cancer cells or cell lines have revealed multiple acid extrusion mechanisms and their involvement in cancer cell growth and progression. In the present study, the role of the sodium bicarbonate transporters (NBCs) in prostate cancer cell proliferation and viability was examined. qPCR revealed heterogeneous expression of five NBC isoforms in human prostate cancer cell lines LNCaP, PC3, 22RV1, C4-2, DU145, and the prostate cell line RWPE-1. In fluorescence pH measurement of LNCaP cells, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(73 reference statements)
0
4
1
Order By: Relevance
“…Because we ruled out any difference in the proliferative rate, cell cycle and apoptosis of pancreatic cancer cells in vitro or an effect on tumor growth in immunocompromised mice, these data indicate that Slc4a4 targeting in cancer cells imposes a cell-extrinsic alteration of the TME that hinders tumor growth and metastasis through the immune system. This might appear in contradiction with in vitro evidence performed in breast, prostate and colorectal cancer cells where Slc4a4 silencing negatively affects cancer cell proliferation [16][17][18] . Unlike other tissues, normal pancreatic duct epithelial cells are exposed to a heterogenous and fluctuating gradient of pH (for example, alkaline in the apical side while acidic in the basolateral side), and, therefore, they might better adapt to pH modifications 50 .…”
Section: Articlecontrasting
confidence: 67%
See 1 more Smart Citation
“…Because we ruled out any difference in the proliferative rate, cell cycle and apoptosis of pancreatic cancer cells in vitro or an effect on tumor growth in immunocompromised mice, these data indicate that Slc4a4 targeting in cancer cells imposes a cell-extrinsic alteration of the TME that hinders tumor growth and metastasis through the immune system. This might appear in contradiction with in vitro evidence performed in breast, prostate and colorectal cancer cells where Slc4a4 silencing negatively affects cancer cell proliferation [16][17][18] . Unlike other tissues, normal pancreatic duct epithelial cells are exposed to a heterogenous and fluctuating gradient of pH (for example, alkaline in the apical side while acidic in the basolateral side), and, therefore, they might better adapt to pH modifications 50 .…”
Section: Articlecontrasting
confidence: 67%
“…Contrasting evidence has proven that the reduction of SLC4A4 expression can both prohibit and promote cancer cell proliferation and migratory traits in vitro or in immunodeficient contexts, largely depending on the tumor cell type [16][17][18][19][20] . Nevertheless, to date, there are no in vivo studies that have examined SLC4A4 as a modulator of tumor pH and antitumor immune responses in pancreatic cancer.…”
Section: Slc4a4 Targeting Inhibits Tumor Growth and Metastasismentioning
confidence: 98%
“…It is widely recognized that LNCaP and C4-2 cells exhibit androgen receptor (AR) positivity, while DU145 and PC3 cells lack AR expression 29 . Previous studies have shown that LNCaP is an androgen-responsive cell line, whereas C4-2, PC3, and DU145 are androgen-independent cell lines 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…1,211 As with primary dRTA, the mechanisms responsible for clinical sequelae of primary pRTA are directly related to the effects of metabolic acidosis and that of specific mutations in transporters. 71 NBCE1 is present in many tissues, 71,212 including the kidney, 213 brain, 214 eye, 215 liver, 216 pancreas, 217 intestine, 218,219 prostate, 220 epididymis, 221 and heart. 222 In the kidney, NBCE1 is responsible for HCO 3 − transport in the proximal tubules.…”
Section: Primary Distal (Type 1) Rtamentioning
confidence: 99%